Botulinum Toxin Type A: Adverse Events and Management - Cavallini, Maurizio; Papagni, Marco; Lazzari, Riccardo; Santorelli, Adriano (Facial Plastic Surgery, 2022)
Aesthetic medicine is witnessing an increasing exploitation of all the procedures. The demand has never been higher than it is today. The number of practitioners is also increasing year by year. Consequently complications and other kinds of related troubles and procedures are also rising. Never like today is fundamental, in case of troubles, how to properly manage with the most frequent issues. In aesthetic medicine field, botulinum toxin procedures are the safest. Lot of patients are worried about botulinum toxin despite the available scientific literature. Rare short-term complications are observed. In the most of cases, nothing severe occurs if the international recommendations and the most recent guidelines are closely followed, the majority of them are injection related. This study is a review of rare or common problems that can occur and how to manage or solve the situations.
Keywords: botulinum toxin; depressor anguli oris; adverse events; safety; Onabotulinum toxin-A